Antropólogos, arqueólogos, imperialismo y la mayanización de Honduras: 1890-1940 - Euraque, Darío A. (2002)
Since the start of the twentieth century, the Honduran state fomented efforts to “mayanize” Honduras. The author links this process with the hegemony of banana interests in that Central America country and the integration of various discourses into a post-colonial national identity.